Sensitivity of mycobacteria to different species of eucalyptus l'herit - Moreira, Raquel R. D. [UNESP]; Anno, Ivone S.; Leite, Clarice Q. F. (My University, 1997)
Sensitivity profile of 10 mycobacteria of clinical interest to eight different species of Eucalyptus L'Herit was studied. A Proportion Method Indirect Test was performed to detect resistant bacilli utilizing 5 and 10 mg/ml of essential oils incorporated to Lowestein-Jensen medium. Mycobaterium tuberculosis and other slow growing mycobacteria were more sensitive to essential oils than faster growing ones. The most effective essential oils, in decreasing order, were Eucalyptus citriodora, Eucalyptus maculata and Eucalyptus tereticornis.
Keywords: Eucalyptus; Mycobacteria; Sensitivity profile